Persepsi Mahasiswa Terhadap Kualitas Pelayanan Akademik Di FKIP Universitas Palangka Raya - Susi Sukarningsi; Alexandro, Rinto; Rani, Wiwin Mustika; Rahman, Rahman; Susan Daniel; Hendrowanto Nibel (Journal Pendidikan Ilmu Pengetahuan Sosial, 2022)
This study aims to determine and analyze students' perceptions of the quality of academic services at the Teaching and Education Faculty, Palangka Raya University. This research uses a descriptive qualitative approach. The selection of respondents was carried out by purposive sampling involving thirteen sources. Data collection procedures were carried out by interviewing, observing and documenting while data analysis was carried out by data reduction, data modeling and drawing conclusions. The results of the study on the quality of academic services which consisted of five dimensions concluded that 1) reliability: inaccurate service, slow service processes, and lack of discipline for academic staff, 2) certainty: knowledge of academic staff in providing good service, good employee skills, and courtesy / hospitality of academic staff is still lacking, 3) tangible: student parking is quite wide but muddy in the rainy season, the waiting room is narrow and stuffy, and only has two chairs for waiting students, 4) empathy: only some academic staff pay attention and concern for students, and 5) responsiveness: lack of responsibility for academic staff. It is hoped that the results of this study can improve the performance of academic staff in providing academic services so that they are faster, more disciplined, prioritize courtesy, improve parking lots and student waiting rooms, care more for students who experience problems, provide suggestion boxes and establish academic service quality standards